Pemberdayaan Kelompok Usaha Pembuatan Keset Kain Dari Limbah Kain Bagi Ibu–Ibu Rumah Tangga Di Kranggan- Bekasi - Laili Savitri Noor; Mulyadi; Trisnani Indriati (SULUH: Jurnal Abdimas, 2019)
Kranggan is an area that will develop because of the many housing developments and supermarkets. From these conditions, many are used by the surrounding community by opening a business to find more income to meet daily needs, especially housewives. Various efforts and development policies have been carried out by the government, especially providing opportunities for the community to improve welfare. Making doormats from fabric waste is one of the empowerment and utilization programs through FEB-UP to the community. This program is carried out by FEB-UP by providing business skills and motivation for Productive Economic activities to improve the social welfare of its members and provide benefits to the surrounding community.